Conversion of Finite Automata to Left Linear Grammar
Converting finite automata to left lienar grammar is somewhat tricky.
See below steps and example followed by it, we will understand the process.
- Take reverse of the finite automata
- Then write right linear grammar following the previous lesson
- Then take reverse of the right linear grammar
- And you will get the final left linear grammar
Take the step 2 output and we will write down "right linear grammar" for it.
Begin from start state, that is B
B -> aB/bB/aA A -> ε
And now reverse the right linear grammar to get the ouput = left linear Grammar
B -> Ba/Bb/Aa A -> ε